Expressive Acts Constructing Religious Identity among Indonesian Muslim Influencers on Instagram (Universitas Islam Negeri Sunan Ampel Surabaya, 2022)
The study investigated the expressive act constructing religious identity among Indonesian Muslim influencers on Instagram. Employing a qualitative descriptive method with non-participant observation, the data were obtained by documenting the caption of the posts from the selected influencers' Instagram accounts, taking notes, and selecting the relevant data. The data were analyzed using Searle's (1976) theory and the identity theory by Thornborrow (2004) to examine how the expressive act constructs religious identity. The results showed seven types of expressive speech acts performed by Indonesian Muslim influencers; Fadil Jaidi, Atta Halilintar, Ria Ricis, and Lesty Kejora. Those expressive speech acts are thanking, gratitude, praise, apology, appreciation, condolence, and congratulation. There are 53 data found, and most of the expressive acts uttered by the influencers are thanking others. Furthermore, the group identities are constructed by the representation of Indonesian Muslim influencers by which the language variations were identified from the code-switching they employed. There are also four common manners practiced by the Muslim influencers: 1) show mercy towards everyone, 2) have respect and love for the elder/ younger, 3) keep good relations with everyone, and 4) be kind to parents.